Factors Relating to Productivity of Fish Unloading Workers - Winda Ayu Suntari; Suroto Suroto; Ekawati Ekawati (Universitas Airlangga, 2023)
Introduction: Tasik Agung Coastal Fishing Port handles the most fish unloading activities in Rembang, which include high and strenuous work with no rest before the activity is completed, long work duration as well as high work demand, work fatigue, work period, and workload. In the professional world, human resources are said to be productive if they complete their tasks and fulfill their responsibilities on time. This study aims to analyze the factors related to the productivity of fish unloading workers. Methods: This study is an analytical observational study applying quantitative method with a cross-sectional approach. The population examined in this study was 100 fish unloading workers. Sampling was carried out offline through the accidental sampling technique, or the determination of samples by chance, in which potential respondents were selected from coincidental meeting with the fish unloading workers. The main data sources are direct measurements of variables, questionnaires, surveys, and interviews. Meanwhile, the secondary data as supporting information were obtained from journals of previous related studies. The data analysis used Spearman's rank correlation test. Results: The study did not find any relationship between work fatigue (p-value = 0.419) and workload (p-value = 0.975) with worker productivity. On the other hand, work period is proven to significantly related to worker productivity (p-value = 0.001). Conclusion: Work fatigue and workload are not related to the productivity of fish unloading workers. Meanwhile, there is a relationship between work periods and worker productivity. The increase in job mastery and work periods are followed by an increase in worker productivity.